Comparison between patient state index, bispectral index, and clinical parameters for propofol induction in Indian patients: A prospective study - Mohammed Shafiq Shajahan; Sanjay Agrawal; Deepak Singla (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Patient state index (PSI) and bispectral index (BIS) are depth of anesthesia monitors utilized for the dosage of propofol usage for induction. We compare PSI, BIS, and Observer's Assessment of Alertness/Sedation Scale (OAA/S) for propofol dose usage for induction. Material and Methods: Seventy-four ASA I and II patients, aged 18-65 years scheduled for laparoscopic cholecystectomy were included and divided into groups to titrate the drug dosage of propofol needed for induction of anesthesia, monitored by PSI (Group A), BIS (Group B), or clinical OAA/S (Group C). The drug dosage needed for induction was based on a PSI value of 25 ± 2, BIS value of 48 ± 2, and OAA/S value of ≤2 as the endpoint of induction in respective groups. Intraoperative hemodynamic variables and any complications were compared. Results: The mean doses of propofol needed for induction were 2.23 mg/kg (Group A), 2.05 mg/kg (Group B), and 2.11 mg/kg (Group C). A significantly decreased dose was needed to achieve the desired end in Group B compared to Group A (P = 0.01). The hemodynamic variables such as heart rate, systolic blood pressure, and diastolic blood pressure among the three groups were comparable. Conclusion: The clinical method of titrating the dose of propofol for induction and anesthetic depth by the loss of verbal response is comparable to both BIS and PSI monitoring.